Digital Da'wah YouTube and Psychological Well-Being Student: A Transformation In Islamic Education In The Contemporary Era - Dwi Nurrahmi; Muslimah Muslimah; Surawan Surawan (SOSIOEDUKASI, 2026)
Digital da’wah content on YouTube shows a significant positive relationship with the psychological well-being of Islamic boarding school students. This study aims to examine the relationship between the intensity of watching da’wah content on YouTube and the psychological well-being (PWB) of students at Ma’had Al-Jami’ah UIN Palangka Raya based on Ajzen’s viewing intensity theory and Ryff’s PWB theory. A mixed-methods approach with an explanatory design was employed. Quantitative analysis results indicate a very strong and significant positive relationship between the intensity of watching YouTube da’wah content and PWB (r = 0.934), accounting for 86.0% of the variance in PWB. These findings indicate that the higher the intensity with which students access YouTube da’wah content, the higher their level of psychological well-being. Qualitative findings reinforce these results by demonstrating the connection between watching YouTube da’wah content, as per Ajzen’s theory, and the reinforcement of the six dimensions of PWB identified by Ryff: self-acceptance, positive relationships with others, autonomy, environmental mastery, life purpose, and personal growth. The contribution of this study to Islamic education is to provide an empirical basis for the utilization of digital da'wah media such as YouTube as a means of religious guidance and the enhancement of the psychological well-being of Islamic university students within the Islamic higher education environment.